Analysing the performance of smallholder cabbage farmers in the southern Philippines - Sarmiento, Jon; Aguinaldo, R.; Digal, L.; Castro, M.; Comidoy, S.; Balgos, C.; Hall, D. (Australian Centre for International Agricultural Research, 2013)
The leading producers of cabbage in southern Philippines are Bukidnon in Northern Mindanao and Davao del Sur in Southern Mindanao. With declining farm-gate prices along with increasing production costs, farmers’ profits are falling. This study examined the productivity, technical efficiency and profitability of farmers situated in these areas. Wholesalers, followed by the farmers, gain the highest net margin among the three actors in the chain considered. Net earnings of the farmers are primarily affected by the two classifications of cabbage—‘good’ or ‘reject’—with the former contributing more to profit. Rejects constitute about 20% of the total production of Bukidnon and 15% of the total production of Davao del Sur farmers. This poor quality produce is associated with limited training in cabbage production and postharvest practices, poor road condition and poor storage facilities. Training could improve farmers’ incomes by 22,026 pesos per cropping season. Productive farmers are described as those who are relatively older and have a higher education level. Among the inputs considered, increasing land area is the primary factor for increasing production. On the other hand, efficient farms are those that are relatively large, at least 1 ha, with older and more experienced farmers located in Kapatagan, Davao del Sur. Quantity of seeds and total cost negatively contribute to the total farm profit, while land area, price of good classification cabbage and total yield are positively contributing to farm profit. Thus, helping farmers generate more profit is not a straightforward approach. It needs an enabling environment such as training and infrastructure. It also takes time, as suggested by age, education and experience variables. Lastly, it takes additional land resources to further increase farmer’s productivity, efficiency and farm profit.